Estudio y diseño de un sistema de detección de incendio en el área de almacenaje en la empresa Triboilgas Cía. Ltda en el año 2016. - Toapanta Valverde, Cristian Andrés (2018)
The project established the study and design of a fire detection system based on NFPA - 72, for Triboilgas Cía. Ltda its activity is to provide oil services supplemented with the best maintenance of heavy is machinery indicated mandatory concepts and terminology of the rules and regulations for fire prevention that will be applied in this design. The absence of a fire detection system in the company's storage area (steel mill, plastics, wood) and are the is events caused by uncontrolled fires caused by human beings, combined with elements of combustion, presented are the approach of the system is of fire detection, which included concepts of the fire alarm code of the Quito Fire Department and are the electrical code according to the Metropolitan Ordinance No. 407 besides containing financial calculations for are the design of the system, accessories and selection of equipment and complementary materials presented in tables with technical specifications plans and recommendations for are the fire detection of this system. He estimated a cost / benefit of the fire detection system in the storage area according to the established regulations, and mainly the design was based on allowing people who perform work or use the storage area and its surroundings in some way necessary security so are that if is there is any kind of fire is inside the site human losses are avoided as well as protecting the structure and raw material in its facilities.